2020
DOI: 10.3390/plants9111538
|View full text |Cite
|
Sign up to set email alerts
|

Use of LAMP for Assessing Botrytis cinerea Colonization of Bunch Trash and Latent Infection of Berries in Grapevines

Abstract: A real-time loop-mediated isothermal amplification (LAMP) assay was evaluated for the detection of Botrytis cinerea in grapevine bunch trash, immature berries, and ripening berries. A simple method for the preparation of crude extracts of grape tissue was also developed for on-site LAMP analysis. When tested with 14 other fungal species frequently found in grapevines, the LAMP assay was specific and sensitive to a B. cinerea DNA quantity of 0.1 ng/µL. The sensitivity was further tested using bunch trash sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…Mumford and Seal [26] reported that yam tissues contain some PCR-inhibitory substances that could be co-extracted with the RNA. This suggests a higher tolerance of RT-LAMP to inhibitors than RT-PCR, which has also been reported in other studies [23,44,45].…”
Section: Discussionsupporting
confidence: 87%
“…Mumford and Seal [26] reported that yam tissues contain some PCR-inhibitory substances that could be co-extracted with the RNA. This suggests a higher tolerance of RT-LAMP to inhibitors than RT-PCR, which has also been reported in other studies [23,44,45].…”
Section: Discussionsupporting
confidence: 87%
“…Investigations of bunch debris at the time of thinning would determine if the fewer debris pieces in the thinned bunches were due to direct shaking of the bunch during the thinning or the removal of individual berries allowing debris to fall from the bunch over time before harvest. New methods of detecting spores in debris and potential spore production [ 85 , 86 ] from the dead plant material in the bunch could be used for a detailed study of the importance of this pathway of infection in the epidemic of vines receiving mechanical shaking or control treatments. If all debris cannot be removed by mechanical shaking and or the use of devices such as the Collard pulsed air system, then other methods to suppress inoculum within the trash such as targeted fungicides or biological control agents [ 35 ] may need to be considered if this pathway is important for harvest disease.…”
Section: Cultural Control Of Bbrmentioning
confidence: 99%
“…Various approaches have been considered for the detection of Botrytis cinerea [3], including gigahertz ultrasonic imaging of fungal spores [4], the fingerprint of the Raman spectrum of the fungal spores [5], detection from the mycelia using antibodies specific for Botrytis species [6], detection of the fungal DNA [7][8][9], or indirect detection through the measurement of indicators such as laccase activity [10], glycerol and gluconic acid [10], or plant hormones (i.e., the combined detection of salicylic, azelaic, and jasmonic acids) [11]. It is important to note that not all strains of Botrytis cinerea produce laccase.…”
Section: Introductionmentioning
confidence: 99%